The Relationship Among thought, Language and Reality in Wilhem von Humboldt’s Linguistic Theory - MSc. Diria Machín-Reyes (Santiago, 2015)
The nineteenth century sets a turning point of linguistics studies based on a historical comparative approach. During this period, it is remarkable the figure of the German Wilhelm von Humboldt, whose first approach to language is characterized by a human philosophical background from an aesthetical and anthropological interest, which take him later to deepen purely linguistic aspects, but keeping certain sociological and cultural sense. Although his work was fully appreciated a century later, it cannot be  denied his influence as a forerunner of some modern theories, particularly those related to descriptive and structural linguistics of different languages. This paper proposes a general view to the main thesis of Humboldt, focused on the relation he establishes among thinking, language and reality in his linguistic theory. Keywords: Humboldt, linguistics, thinking, language, society.